DNA in extracellular vesicles: biological and clinical aspects - Elzanowska, Julia; Semira, Christine; Costa‐Silva, Bruno (Molecular oncology, 2021)
The presence of DNA in EVs, including exosomes and microvesicles, remains contentious as this field of study is still evolving. This review explores what is known about the biogenesis of EV‐DNA and the possible biological roles of DNA packaging into EVs. Moreover, we also discuss the potential clinical applications of EV‐DNA and how those compare to cell‐free DNA. The study of extracellular vesicles (EVs), especially in the liquid biopsy field, has rapidly evolved in recent years. However, most EV studies have focused on RNA or protein content and DNA in EVs (EV‐DNA) has largely been unnoticed. In this review, we compile current evidence regarding EV‐DNA and provide an extensive discussion on EV‐DNA biology. We look into EV‐DNA biogenesis and mechanisms of DNA loading into EVs, as well as describe the particularly significant function of DNA‐carrying EVs in the maintenance of cellular homeostasis, intracellular communication, and immune response modulation. We also examine the current role of EV‐DNA in the clinical setting, specifically in cancer, infections, pregnancy, and prenatal diagnosis.